The importance of timing in energy shipping: A case from Cyprus - Olga Kandinskaia; Sergey Dobrinov; Ioannis Filippopoulos (The Central European Review of Economics and Management (CEREM), 2024)
Aim: Investment decisions in shipping are notoriously difficult. The key reason is that freight rates are highly volatile and often unpredictable. The energy shipping sector is most challenging. The paper formulates an investment decision rationale in energy shipping and provides insights as to the ability of experts to predict market trends when it comes to the oil tanker supply and demand and the resulting freight rates. Moreover, we focus on the timing of such investment decisions and ways to identify when the timing thereof is right. This paper aims to develop an investment decision framework in energy shipping, specifically investigating the importance of timing when making investment decisions in this sector, and to test the suggested rationale by applying it to a specific oil tanker purchase case. Design / Research methods: The research process started with a Delphi study to gather expert opinions on the changes taking place in the shipping market. We continued our research process with a concise economic analysis of the 2018 shipping market, and we then applied the findings to a feasibility study for purchasing a specific type of small-scale (Aframax) oil tanker by a company based in Cyprus. Conclusions / findings: Our main findings were that the opinions of the selected commercial experts supported the results of the secondary data analysis, and all the respondents found the year 2018 an attractive time for investing in ships. The results of an investment appraisal financial modelling exercise for the above-mentioned specific purchase case were satisfactory for accepting the project. Due to low purchase prices and high residual value, the initial required investment was lower while the return and other results would be better for a 15-year-old ship than for a 10-year-old unit. However, the risks were to increase together with age. Considering that the prices of Aframaxes were hitting their historically low levels in 2018, and that within the next five years the demand for modern tonnage was anticipated to be firm and thus raise their values up to 35% above the 2018 levels, the purchase of a more modern unit was recommended as it could give an opportunity of a beneficial resale at the end of the project or earlier. In view of the latest market developments, we can now conclude that overall, despite the unprecedented turbulence during the pandemic years, the 2018 investment recommendation proved correct and insightful. Originality / value of the article: The current paper's intended contribution is an investment analysis based on the primary data from a relatively small shipping company. The disclosed primary data for the intended 2018 purchase of an Aframax oil tanker is unique. Thus, the current paper provides useful practical guidance for potential investors and other professionals who follow the energy shipping market as well as contribute to academic research in shipping finance by providing a framework that is applicable well beyond the described case study. Considering the upward move in the crude oil freight rates and anticipating investment interest in energy shipping, following the Covid-19 pandemic and the war between Russia and Ukraine, we believe that this research paper has a good timing.
Keywords: F44; G31; L22; L91; R42; 330; crude oil transfer services; decision making; energy shipping; freight transport; Investment project